Biomimetic Hyaluronan Binding Biomaterials to Capture the Complex Regulation of Hyaluronan in Tissue Development and Function - Amelia Huffer; Mingyang Mao; Katherine Ballard; Tugba Ozdemir (Biomimetics, 2024)
Within native ECM, Hyaluronan (HA) undergoes remarkable structural remodeling through its binding receptors and proteins called hyaladherins. Hyaladherins contain a group of tandem repeat sequences, such as LINK domains, BxB7 homologous sequences, or 20–50 amino acid long short peptide sequences that have high affinity towards side chains of HA. The HA binding sequences are critical players in HA distribution and regulation within tissues and potentially attractive therapeutic targets to regulate HA synthesis and organization. While HA is a versatile and successful biopolymer, most HA-based therapeutics have major differences from a native HA molecule, such as molecular weight discrepancies, crosslinking state, and remodeling with other HA binding proteins. Recent studies showed the promise of HA binding domains being used as therapeutic biomaterials for osteoarthritic, ocular, or cardiovascular therapeutic products. However, we propose that there is a significant potential for HA binding materials to reveal the physiological functions of HA in a more realistic setting. This review is focused on giving a comprehensive overview of the connections between HA’s role in the body and the potential of HA binding material applications in therapeutics and regenerative medicine. We begin with an introduction to HA then discuss HA binding molecules and the process of HA binding. Finally, we discuss HA binding materials anf the future prospects of potential HA binding biomaterials systems in the field of biomaterials and tissue engineering.